Small margin excision of periocular basal cell carcinomas. Issue 6 (19th March 2009) - Chadha, V; Wright, M
Abstract : Aims: To analyse the outcome of small margin (up to 2 mm) excision of primary clinically well-defined periocular basal cell carcinomas (BCCs). Methods: Retrospective evaluation of 90 well-demarcated primary BCCs having a minimum follow-up of 36 months. All patients underwent excision of the tumour with maximum margins of 2 mm. Resulting defects were, if possible, closed directly. Reconstruction of defects requiring flaps or grafts was delayed until receipt of the histological report which was obtained in all cases. Results: One-stage excision and direct closure was performed in 67 patients (74.4%). In 23 patients (25.6%) reconstruction was delayed by 4 days to enable receipt of the histopathology report. Histological assessment confirmed complete excision after the first excision in 78 (86.7%) rising to 83 (92.2%) after two excisions. The mean follow-up was 47.5 (SD 9.1) months. Of the 12 cases with incompletely excised lesions, seven of the patients chose not to have any more surgery, and only one of these recurred. There were two other recurrences, and in both of them the lesion had initially been reported as completely excised. Overall the recurrence rate in our study was 3.3% (n = 3). Conclusions: Our recurrence rate compares well with published results following conventional excision of BCCs. In the absence of availability of Mohs surgery, well-demarcated nodular basal cell carcinomas can be safely excised using smaller margins than conventionally practised.